A grammar of Yauyos Quechua - Shimelman, Aviva (Studies in Diversity Linguistics, 2017)
This book presents a synchronic grammar of the southern dialects of Yauyos, an extremely endangered Quechuan language spoken in the Peruvian Andes. As the language is highly synthetic, the grammar focuses principally on morphology; a longer section is dedicated to the language's unusual evidential system. The grammar's 1400 examples are drawn from a 24-hour corpus of transcribed recordings collected in the course of the documentation of the language.